Geological setting, mineralogy and geochemistry of plutonic rocks and related auriferous quartz veins in the Baskil region Elazig, Eastern Turkey - Akgül, M; Bölücek, C; Sagiroglu, A (Springer India, 2003)
Baskil auriferous quartz veins are found in granitoids of Coniacian-Campanian age. The granitoids, together with gabbro, volcanics, subvolcanics and pyroclastics constitute the Elazig Magmatic Complex. These have characteristics typical of arc magmatics, and are thought to be related to S-N subduction during closure of the Tethys. The geochemical investigations in this study indicate that some parts of the Elazig Magmatic Complex have similar composition to that of syn-COL granitoids, and these rocks-are ascribed to a separate Baskil pluton. Quartz veins occurring within the Baskil Pluton extend into other lithologies of the Elazig Magmatic Complex. The veins are 0.2 - 2.0 m thick and are up to several hundred metres in length. They occupy NW-SE striking fractures and display narrow wall rock alteration zones. From surface downwards the wall rock alteration changes from sericitization through pyrophylitic alteration to secondary K-feldspar formation. Silicification is common and is observed around all veins. The main component of the veins is quartz and sulphide minerals are concentrated as lumps among quartz crystals. The ore minerals within the veins are cubanite, chalcopyrite, arsenopyrite, tetrahedrite-tennantite, bismuthinite, sphalerite and native Au. The veins are closely related to the Baskil Pluton and were probably the final products of plutonic evolution. High temperature ore minerals (cubanite, bismuthinite), wall rock alteration (secondary K-feldspar, pyrophylitic alteration), and spatial relations of veins with the pluton, all indicate a nearby source for the hydrothermal solutions which formed the quartz veins. The metals were probably derived from magmatic fractionation and Au was transported as sulphide complexes.
Keywords: quartz veins; gold mineralisation; syn-COL granitoids; Elazig Magmatic Complex; Eastern Turkey